Is there a delay in seeking medical care after the first seizure in “resource limited settings”: a pilot study from Sri Lanka - Herath, H. M. M. T. B. (BMC Res Notes, 2018)
OBJECTIVES: Current guidelines suggest that patients presenting with the first seizure should be assessed by a specialist, preferably with investigations such as electroencephalography and imaging to reach a definitive diagnosis. We conducted a cross sectional study among patients with confirmed epilepsy, at a tertiary level neurology clinic in Sri Lanka with the aim of assessing delays in first contact with a medical doctor and in performing key investigations after the first seizure. RESULTS: Majority had sought medical attention within 24 h of the first seizure (71.2%) and had seen a specialist within the 1st week since the seizure (61%). Also a significant proportion had completed key investigations such as electroencephalography (63.2%) and brain imaging within a month (51%) since the first medical consultation. Of many socio-demographic and illness related factors examined, only a non-generalized tonic–clonic presentation was significantly associated with delay in seeking medical help.